Pembelajaran Dinamika Implementasi Pembelajaran Al-Qur'an Metode Tilawati Ramah anak : Studi Implemntasi Pembelajaran Al-Qur'an Metode Tilawati Ramah Anak di TPQ Al-Ikhlash Detasasri Waru Sidoarjo - Ainun Nadlif; Arif, M Lukman; Handayani, Puspita; Maulana, Ilyas (UII, 2024)
Learning the Qur'an today employs various methods and approaches in practice. Teaching and learning activities in Islamic educational institutions are required to be dynamic and contextual. The Tilawati method of learning, as one of the methods for studying the Qur'an, is a learning method that must continue to be developed to align with the current era and educational trends. Additionally, implementing the Tilawati method in teaching and learning activities can create a child-friendly environment. The aim of this community service project is to study the implementation of the child-friendly Tilawati learning method at TPQ Al-Ikhlash Waru Sidoarjo and to develop a child-friendly learning concept based on children's character values. The community service approach utilizes a case study method. The subjects of the community service are the teachers (Asatidz and Asatidzah) and students (santri) of TPQ Al-Ikhlash Waru Sidoarjo. Data collection methods include interviews, observations, and documentation. Data analysis is performed using descriptive analysis. Field findings indicate two categories related to the implementation of the child-friendly Tilawati method at TPQ Al-Ikhlash Waru: first, the concept of a child-friendly school involves inclusive learning, environmentally friendly learning, social education, and justice-based education; and second, Qur'anic learning that is relevant to the children's world.